Design of an automatic antenna tuner - Siti Afifah , Hassan (2013)
This thesis presents the design of an Automatic Antenna Tuner. Automatic Antenna Tuner is used to improve the power transfer on the transmission line by matching the impedance of the tuner to antenna. It attempts to convert the input impedance to 50 to matching with the antenna impedance. It is also used to control the switching components to load the signal frequency. The objectives of this project are to develop the software system to control the switching components, to develop an LC circuit and to find the best combination of inductor and capacitor to load the signal frequency. This thesis describes the development of the automatic antenna tuner and the criteria needed to develop the equipment. The range of frequency, that the automatic antenna tuner able to load is 323MHz.